Distribution of bioactive factors in human milk samples - Reka A. Vass; Agnes Kemeny; Timea Dergez; Tibor Ertl; Dora Reglodi; Adel Jungling; Andrea Tamas (International Breastfeeding Journal, 2019)
Abstract Background Breast milk provides nutrition for infants and also contains a variety of bioactive factors that influence the development of the newborn. Human milk is a complex biological fluid that can be separated into different layers (water phase and lipid phase with its component water and lipid fractions). It can affect the developing human body along the whole length of the gastrointestinal tract, and through the circulation, its factors may reach every organ. Methods In the present study, we analyzed milk samples collected monthly for 6 months from 16 mothers from the 4th week postpartum between 2014 and 2016 in Baranya County, Hungary. The 96 samples provided us information about the fluctuation of certain bioactive factors during the first 6 months of lactation. We investigated with Luminex technology the concentrations of several cytokines (CD40, Flt-3L), chemokines (MCP-1, RANTES, GRO, MIP-1ß, MDC, eotaxin, fractalkine), and epidermal growth factor (EGF). Paired t-tests and one-way ANOVA followed by Bonferroni post-hoc tests were used to compare the data. Results We detected the presence of each bioactive factor in every layer of the milk samples during the first 6 months of breastfeeding in widespread concentration ranges. In the case of GRO, MIP-1ß, MDC, Flt-3L, fractalkine, and eotaxin, the concentrations were constant during the first 6 months of lactation. The water phase of human milk contained higher factor concentrations compared to both fractions of the lipid phase for most factors (except eotaxin and MIP-1ß). The concentrations of CD40, EGF, MCP-1, and RANTES in the first 3 months were significantly different compared to the values detected between 4th and 6th months. In the water phase, the level of MCP-1 was significantly decreased, while all of the other factors increased during the 4th through 6th months. We found significantly higher EGF, GRO, and RANTES levels in the water fraction compared to the lipid fraction of the lipid phase. Conclusions The novel findings of this investigation were the presence of Flt-3L and MDC in all layers of breast milk, and nearly all bioactive factors in the lipid phase. Due to their widespread physiological effects these factors may have an essential role in organogenesis.